Transcriptional host–pathogen responses of Pseudogymnoascus destructans and three species of bats with white-nose syndrome - Christina M. Davy (Taylor & Francis Group, 2020)
Understanding how context (e.g., host species, environmental conditions) drives disease susceptibility is an essential goal of disease ecology. We hypothesized that in bat white-nose syndrome (WNS), species-specific host–pathogen interactions may partly explain varying disease outcomes among host species. We characterized bat and pathogen transcriptomes in paired samples of lesion-positive and lesion-negative wing tissue from bats infected with Pseudogymnoascus destructans in three parallel experiments. The first two experiments analyzed samples collected from the susceptible Nearctic Myotis lucifugus and the less-susceptible Nearctic Eptesicus fuscus, following experimental infection and hibernation in captivity under controlled conditions. The third experiment applied the same analyses to paired samples from infected, free-ranging Myotis myotis, a less susceptible, Palearctic species, following natural infection and hibernation (n = 8 sample pairs/species). Gene expression by P. destructans was similar among the three host species despite varying environmental conditions among the three experiments and was similar within each host species between saprophytic contexts (superficial growth on wings) and pathogenic contexts (growth in lesions on the same wings). In contrast, we observed qualitative variation in host response: M. lucifugus and M. myotis exhibited systemic responses to infection, while E. fuscus up-regulated a remarkably localized response. Our results suggest potential phylogenetic determinants of response to WNS and can inform further studies of context-dependent host–pathogen interactions.